STRUKTUR KOMUNITAS FITOPLANKTON DI LOKASI TAMBAK KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Sucika Armiani (Bioscientist : Jurnal Ilmiah Biologi, 2015)
Sekotong is one of West Lombok subdistricts with considerable potential for marine fisheryled to the development of aquaculture businesses. The purpose of this study were to know the phytoplankton community structure. The methods used field survey for three months, started from June to August 2014. Sampling was done by purposive sampling that consisted of 3 stations, with 3 substations on each station. Samples were analyze dinsituand in laboratory. Results showed that the abundance of phytoplankton ranged from 449-3966 ind/l. Index of diversity on all three stations were classified as medium/moderate. Uniformity index of phytoplankton was high and there was no species dominance.